KEBIJAKAN FORMULASI HUKUM PIDANA DALAM PENANGANAN TINDAK PIDANA DI BIDANG TINDAKAN MEDIK - Sonya Airini Batubara; Mahmud Mulyadi; Marlina Marlina; Suhaidi Suhaidi (USU LAW JOURNAL, 2016)
ABSTRACT   Medical personnel looks like doctor is a profession devoted to the science of public interest, to have freedom of humanitarian values under the code of medical ethies. The use of penal law is penal law policy’s problem. Penal law policy can be seen from functional aspect. There are three steps in penal law processing i.e. formulation, application and execution. Formulation step or known as legislative policy is strategic step because the regulation is being decision. So the research will be conducted to policy formulation of criminal law in the handling of criminal acts in the field of medical treatment. The results of this study are action of medical services as a criminal offense under code of criminal law, code of criminal procedure law, Act No. 29 of 2004 on Practise of Medicine, Act No. 36 of 2009 on Health and Act No. 44 of 2009 on Hospital are actions that meet the elements of the error, the rules regarding the health law is not fully set up explicitly and accomodate issues that arise in this field of health care, and regarding legal protection for victims of crime in the field of medical services performed by imposing sanctions for criminal. Based on this research is suggested for improvement of the education system to the performance of the medical supervision, completion of the rule of law and health law enforcement officers, and revised formulation of legislation in the medical field. Key words: Policy formulation, Criminal law, Medical services.